Hubungan Pengetahuan Ibu Hamil Tentang Persalinan Dengan Tingkat Kecemasan Di Puskesmas Kampung Melayu - T, Gloria Nauli; DL, Manggiasih; OL, Tetty; Emilia, Emilia (STIKes Medistra Indonesia, 2026)
Anxiety in pregnant women is a common health problem during pregnancy and can impact the physical and psychological well-being of the fetus. One factor suspected of being associated with maternal anxiety is knowledge about childbirth. Good knowledge is expected to help pregnant women prepare physically and mentally for the birth process. This study aims to determine the relationship between maternal knowledge about childbirth and anxiety levels at the Kampung Melayu Community Health Center. This research is a quantitative, correlational analytical design using a cross-sectional approach. The population was all pregnant women attending antenatal visits at the Kampung Melayu Community Health Center. The sampling technique used was total sampling. Data collection was conducted using a childbirth knowledge questionnaire and an anxiety level questionnaire. Data analysis was performed using the Spearman Rank test. The results showed a p-value > 0.05, indicating no significant relationship between pregnant women's knowledge about childbirth and anxiety levels. The conclusion of this study is that pregnant women's knowledge is not significantly related to anxiety levels. Other factors such as previous childbirth experience, parity, childbirth history, and family support are suspected to have a greater influence on pregnant women's anxiety.